The Intentionality of Confronting Racism, Systemic Oppression, and Cyclical Trauma in Counselor Education: A Self Study - Kara Ieva; Michael D. Hannon; Linwood G Vereen (Teaching and Supervision in Counseling, 2021)
Utilizing self-study methodology, the researchers sought to understand their practices in developing school counselors and counselor educators who acknowledge and resist anti-Black racism and marginalization to prevent harm through complacency. Given counselor education’s existence as overwhelmingly white and Eurocentric, the authors investigate disrupting the heteronormative structures inherent in counseling and the academy with the prioritizing of race, systemic inequities, and cyclical trauma in their faculty roles (e.g., teaching, supervising, and service) in efforts to shift a profession slow to address society’s ever-changing mental health needs. The team of counselor educators from different states in the northeast use a thematic analysis to highlight their challenges and successes at each institution, and within the broader counselor education and academic context.
Keywords: self-study; counselor education; social justice counseling; decolonizing; racism